Nutrigenomics: A Budding Cross-Over - Aggarwal, Navidha; Rohit Malik; Mittal, Arun; Tushir, Shiva; Chopra, Shivani; Chopra, Hitesh (Scripta Medica, 2025)
Nutrigenomics is a rapidly developing subject that combines genomics and nutrition to reveal the complex interactions between our genetic composition and the foods we consume. This review paper provides a thorough overview of nutrigenomics, exploring its underlying theories, methods and significant implications for customised nutrition and healthcare. The goal of nutrigenomics is to understand the molecular processes underlying the diverse ways in which people respond to different diets by examining the dynamic interplay between an individual’s genetic profile and the nutrients they ingest. To provide a sophisticated knowledge of the genetic elements that contribute to the variation in human reactions to dietary components, this inquiry starts with an explanation of the fundamental concepts of genetics and genomics. The review paper continues to describe the approaches used in nutrigenomic research, with a focus on using state-of-the-art technology like bioinformatics and high-throughput sequencing. These instruments enable scientists to unravel the intricate connections between genetic variants and dietary components, leading to a more sophisticated understanding of how our genes regulate our reactions to particular foods. Nutrigenomics key component is its ability to open the door to customised nutrition. Practitioners are able to customise dietary advice for each patient based on their distinct genetic predispositions by analysing their genetic code. The one-size-fits-all strategy is superseded by this method, recognising the innate genetic variability affecting how our bodies metabolise and react to various nutrients. This review article covers current research findings, shedding light on the potential of nutrigenomics to revolutionise disease management through precision nutrition.